Genome-wide association study based on cardiac magnetic resonance imaging in 23, 634 individuals identifies five new loci associated with left atrial enlargement. (25th November 2020) - Ahlberg, G; Andreasen, L; Ghouse, J; Haunsoe, S; Svendsen, J.H; Olesen, M.S
Abstract:  : Left atrial enlargement is associated with mortality due to cardiovascular disease and all-cause mortality. The pathology behind and the association with cardiovascular outcomes are, however, poorly characterised. Compromised atrial function seems to predispose for stroke. We obtained data from the UK Biobank cardiovascular magnetic resonance (CMR) protocol containing CMR scans from ∼31, 000 individuals at the time of study (Fig. 1a). Genome-wide association studies were carried out on state-of-the-art imaging variables exposed to machine learning algorithms to investigate the genetic basis of left atrial volume and function. Deep learning algorithms segmented the atria in the CMR scans (Fig. 1b). Left atrial (LA) volume curves could then be extracted and analysed (Fig. 1c). We tested 10.6 million variants for association with LA minimum/maximum volumes and LA emptying fraction (LAEF) in 23, 624 European individuals without prevalent myocardial infarction or heart failure. We identified five genetic loci located in close proximity to the genes EIF2D, C9orf3, ANKRD1, FGFR2, and MYO18B. We observed a notable genetic correlation between both maximum and minimum LA volumes and stroke and cardioembolic stroke (Fig. 1d). Conclusions: We report on five genetic loci and suggest several plausible candidate genes important for atrial structural pathology. Genetic correlation analyses indicate that the genetic determinants of LA volumes could be markers of stroke risk. These findings enhance our understanding of the importance of the LA and are potential novel therapeutic targets for cardiovascular disease, including stroke. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Novo Nordisk, Halles Moeller